PERAHU SANDEQ; MAKNA USSUL DAN PEMALI DALAM PROSESI PEMBUATANNYA - Ulya Sunani (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This article examines the meaning contained in ussul and pemali associated with the procession of making sandeq boats . To study descriptive qualitative methods are used. The data analyzed are oral data relating to the procession of making sandeq boats which were obtained through in-depth interviews with Mandar sailors, boat builders and religious figures /clerics who were informants, including community leaders. The results of the analysis showed that the ussul and pemali of the Mandar tribe were related to the procession of making sandeq boats which involved rituals in the form of objects, symbols and meaningful behavior. It was concluded that ussul and pemali further reinforced that the sandeq boat was part of the identity of the Mandar tribe. The Ussul and Pemali meanings illustrate the hope and orientation of safety and the good fortune which is a form of love of the Mandar tribe for the sandeq and the sea.